GAMBARAN PENGETAHUAN IBU TENTANG PIJAT BAYI DI DESA RAMBAH TENGAH HILIR KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Sri Wulandari (Fakultas Ilmu Kesehatan, 2021)
ABSTRACT Baby massage is a health treatment in the form of touch therapy with certain techniques given to babies so that treatment and therapy can be achieved. physically and psychologically. Do baby massage regularly in order to maintain his health. Moreover, baby massage has many benefits, namely making babies calmer, increasing the effectiveness of sleeping rest, improving baby's concentration and increasing milk production. knowledge will increase according to the process of experience experienced. The author's aim is to determine the description of mother's knowledge about baby massage in Rambah Tengan Hilir Village, Rambah Hilir District, Rokan Hulu Regency in 2021. The type of research used is descriptive research with a cross sectional research design. The population in this study is mothers. who have babies aged 1-10 months. The sampling technique used was Total Sampling with a sample size of 50 people. data collection using a questionnaire with 20 questions. Data analysis using univariate analysis. The results of the analysis showed that the mother's knowledge about infant massage had sufficient knowledge of the majority as many as 27 people (54.0%), Good as many as 16 people (32.0%), Less as many as 7 people (14.0%). Health workers, especially in the village of Rambah, strive to improve services for infants and toddlers, especially baby massage and often provide counseling to mothers, what is the meaning, benefits, and techniques of baby massage to mothers who have babieshow to do a good massage. Keywords: Knowledge, Mother, Baby Massage